The Relationship between Peer Group Social Support and Academic Burnout among Students at SMAN 1 Bae Kudus in the 2025/2026 Academic Year - Aulia Nisa’ Cahya Ningrum; Sucipto Sucipto; Agung Slamet Kusmanto (SAINTIS Publishing, 2025)
This study aims to uncover the relationship between social support provided by peer groups and the level of academic burnout experienced by tenth-grade students at SMAN 1 Bae Kudus in the 2025/2026 academic year. The background of this study is based on the high academic pressure experienced by students and the importance of social interaction within peer groups as a supportive factor in coping with stress and preventing academic burnout. It is hoped that the results of this study can serve as a reference in designing peer-based social support intervention programs. This study is based on Sarafino's (1998) theory of social support, which divides social support into five categories: emotional, esteem, instrumental, informational, and social network. Meanwhile, the understanding of academic burnout refers to the concept developed by Maslach and Jackson, which categorizes burnout symptoms into three aspects: emotional exhaustion, cynical attitudes toward academic activities, and low self-efficacy in learning. These two theories serve as the primary framework for evaluating the role of peer groups in reducing the risk of academic burnout. The method used in this study is a quantitative approach with a correlational research design. The participants in this study were randomly selected tenth-grade students at SMAN 1 Bae Kudus. The data collection instruments were the Multidimensional Scale of Perceived Social Support (MSPSS) questionnaire to measure perceptions of social support and the Maslach Burnout Inventory-Student Survey (MBI-SS) to measure levels of academic burnout. Data analysis was conducted using Pearson's correlation technique with SPSS software. The results of the analysis showed a significant negative correlation between peer social support and academic burnout levels, meaning that the higher the social support received, the lower the level of burnout in academic activities.